Shock Tube as an Impulsive Application Device - Soumya Ranjan Nanda; Sumit Agarwal; Vinayak Kulkarni; Niranjan Sahoo (International Journal of Aerospace Engineering)
Current investigations solely focus on application of an impulse facility in diverse area of high-speed aerodynamics and structural mechanics. Shock tube, the fundamental impulse facility, is specially designed and calibrated for present objectives. Force measurement experiments are performed on a hemispherical test model integrated with the stress wave force balance. Similar test model is considered for heat transfer measurements using coaxial thermocouple. Force and heat transfer experiments demonstrated that the strain gauge and thermocouple have lag time of 11.5 and 9 microseconds, respectively. Response time of these sensors in measuring the peak load is also measured successfully using shock tube facility. As an outcome, these sensors are found to be suitable for impulse testing. Lastly, the response of aluminum plates subjected to impulsive loading is analyzed by measuring the in-plane strain produced during deformation. Thus, possibility of forming tests in shock is also confirmed.